L’influence des Réseaux Sociaux Numérique sur le Comportement d’achat du Consommateur - Abelhak, Soumia; Baraka, Hayat; Graa, Amel (جامعة الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2016)
This research aims to understand how the online social networks (OSN) can affect the purchase behavior of Algerian consumer. This study presents a quantitative survey among 350 OSN’ users. The research uses structural equation modeling (SEM) with the PLS approach (Partial Least Square) to analyze and confirm the conceptual model proposed in the study. The results confirm that the OSN influence the intention of purchase of the internauts notably through the personal factors as the commentaries and the opinions let on the products and the marks. From these results; it appears necessary for the Algerian companies to integrate the social E-commerce in their marketing strategies in order to make know and to sell their products and services.
Keywords: الانترنت -- الشبكات الاجتماعية -- سلوك المستهلك -- التجارة الإلكترونية